A percepção dos profissionais de saúde em relação à higienização das mãos - Adriana Cristina de Oliveira (2017)
Objective: To verify aspects related to the perception of healthcare workers regarding hand hygiene. Methods: Cross-sectional study in a emergency care unit at a university hospital in Belo Horizonte. A structured questionnaire was applied to nursing and medical staff. The statistic program SPSS was used, descriptive and univariate analysis were made. Results: Healthcare workers attributed as high the impact of infections on clinical evolution of patients and the effectiveness of hand hygiene in controlling those infections. The rate for self-reported compliance to hand hygiene was 76.0% for the nursing staff and 72.5% for medical staff, but lower than 60.0% for coworkers. Conclusions: Healthcare workers perceive hand hygiene as an effective measure to control infection and recognize that compliance rates of hand hygiene among health teams in general are low.